Marketing and management models of China`s table tennis association membership system - Jin, Y.; Zhuofang, D. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The present study explores the membership system of the Chinese Table Tennis Association (CTTA), with respect to status, characteristics, rules and marketing trends of the system. The aim was to develop marketing and management models to fit the development of the market economy and ensure membership rights protection, in order to effectively promote the expansion of table tennis as a sport for all.